Perceived social support and depression among people living with HIV in China: roles of stigma and adherence self-efficacy - Pengfei Wang; Jianjing Xiong; Jinlei Zheng; Chengliang Chai; Ying Wang (BMC Psychiatry, 2023)
Abstract Introduction People living with HIV (PLHIV) are a high-risk group for depression. In particular, the prevalence and burden of depression is higher and more severe among PLHIV in developing and less-developed countries. There is evidence that perceived social support has a positive impact on reducing the occurrence of depression, and high stigma and low adherence self-efficacy are barriers to the effectiveness of social support for depressed PLHIV. However, how these risks affect the effect of social support on depression still needs further identification. Methods Between 2017 and 2018, a total of 1139 Chinese PLHIV (74.36% male, mean age = 43.91 years) from three provinces (Shanghai, Zhejiang and Henan) in China were enrolled in the study. Data were analyzed by multiple regression, mediation model, and moderation model. Results A total of 43.99% of PLHIV had mild to severe depression. There was a significant negative association between perceived social support and depression (B = -0.049, P < 0.05). Stigma and adherence self-efficacy played a chain mediating role (B = -0.058, 95% CI: -0.078 ~ 0.039) and a moderating role in the effect of perceived social support on depression (stigma: B = -0.003, P < 0.05; adherence self-efficacy: B = 0.004, P < 0.05). Conclusion Stigma and adherence self-efficacy indirectly predicted depression, and perceived social support was more effective in reducing depression among PLHIV with high stigma or low adherence self-efficacy. Enhancing multiple social support resources for PLHIV may reduce their risk of depression. Moreover, the need for social support is greater for those with high stigma or low adherence self-efficacy.